Heme Oxygenase 1 and 2 Common Genetic Variants and Risk for Essential Tremor. Issue 24 (June 2015) - Ayuso, Pedro; Agúndez, José A.G.; Alonso-Navarro, Hortensia; Martínez, Carmen; Benito-León, Julián; Ortega-Cubero, Sara; Lorenzo-Betancor, Oswaldo; Pastor, Pau; López-Alburquerque, Tomás; García-Martín, Elena; Jiménez-Jiménez, Félix J.; Das., Undurti Narasimha
<x xml:space="preserve">Abstract</x> Abstract Several reports suggested a role of heme oxygenase genes 1 and 2 (HMOX1 and HMOX2) in modifying the risk to develop Parkinson disease (PD). Because essential tremor (ET) and PD share phenotypical and, probably, etiologic factors of the similarities, we analyzed whether such genes are related with the risk to develop ET. We analyzed the distribution of allelic and genotype frequencies of the HMOX1 rs2071746, HMOX1 rs2071747, HMOX2 rs2270363, and HMOX2 rs1051308 single nucleotide polymorphisms, as well as the presence of copy number variations of these genes in 202 subjects with familial ET and 747 healthy controls. Allelic frequencies of rs2071746T and rs1051308G were significantly lower in ET patients than in controls. None of the studied polymorphisms influenced the disease onset. The present study suggests a weak association between HMOX1 rs2071746 and HMOX2 rs1051308 polymorphisms and the risk to develop ET in the Spanish population.